STAFF SCHEDULE ANALYSIS OF PHARMACY SERVICES USING SIMULATION CASE STUDY: MEDIKA ANTAPANI REGULAR - Mustain, Khabib; Basri, Mursyid Hasan (Journal of Business and Management, 2017)
Abstract. Background: Appropriate and good services are one of tools or strategy to guarantee customer satisfaction. As well-known medicine provider in Bandung, Regular Pharmacy want to increase their service quality using strategy to reduce the customer waiting time in the process of pharmacy services. To know the waiting time, the data about service time and the number of available staff are seriously needed. The number of staff has high impact to waiting time because as long as the number of staff increase the capacity increase respectively. The problem occurred here is, Regular Pharmacy have no clear standard about when staff schedule started and end also has no real reason for staff schedule decision. Methods: To answer the condition, this research use time study to record service time on the Regular Pharmacy. Then, recorded time will be analyzed using control chart, in order to know whether the process is in control or not. This activity uses Minitab software. Then, next process represents the business process in Regular Pharmacy using iGrafx software. After all, data collected including the number of demand, the next process is run the process business simulation using the IGrafx software. Results:  The output of this research is cycle time of pharmacy services and human resources allocation in the Regular Pharmacy. Therefofrom the simulation the information about when staff has to be added or reduced regarding the number of dem re, and. Conclusion: The waiting time decrease and human resources utilization increase and staff schedule could be better.  Keywords:  pharmacy services, time study, staff schedule, simulation, business process